Children's participation in the preschool classroom: an an ethnographic case study - Erbil, Fetiye. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
This study aims to understand how young children participate in a preschool classroom and what the teachers’ role is in promoting children’s participation. The study also looks at teachers’ image of the child and childhood, how the school is governed and how the administration positions itself in terms of children’s rights. The study has the goal of including children and their voices in the research process and in doing so, children’s agency and competence are aimed to be underlined. The study is conducted as an ethnographic case study in a private preschool classroom in Istanbul. Fifteen children who are five or six years old, four teachers and one school principal took part in this research. The classroom observations, interviews with teachers and children and reflection notes are used as the data of the study. The data is analyzed through thematic content analysis. The analysis has led to the development of a participation model. The model proposes that there are many factors that interact with each other and determine the participation of children in this preschool classroom.
Keywords: Preschool children.; Preschool teachers.